2020
DOI: 10.3390/plants10010009
|View full text |Cite
|
Sign up to set email alerts
|

Development and Application of Gene-Specific Markers for Tomato Yellow Leaf Curl Virus Resistance in Both Field and Artificial Infections

Abstract: Tomato yellow leaf curl virus (TYLCV) is a disease that is damaging to tomato production worldwide. Resistance to TYLCV has been intensively investigated, and single resistance genes such as Ty-1 have been widely deployed in breeding programs. However, resistance-breaking incidences are frequently reported, and achieving durable resistance against TYLCV in the field is important. In this study, gene-specific markers for Ty-2 and ty-5, and closely-linked markers for Ty-4 were developed and applied to distinguis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Molecular markers linked to potential resistance loci can provide information for early selection and are useful for breeding horticultural crops resistant to viruses [ 47 ]. Several molecular markers associated with virus resistance loci in pepper and tomato has been developed to expedite marker-assisted breeding [ 48 , 49 ]. Introgression of resistance genes into cultivated varieties has been the principal route of breeding cultivars that are resistant to viruses such as Tomato yellow leaf virus (TYLCV), Tomato spotted wilt virus (TSWV), Pepper yellow leaf curl virus (PepYLCV) and Chilli veinal mottle virus (ChiVMV) [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular markers linked to potential resistance loci can provide information for early selection and are useful for breeding horticultural crops resistant to viruses [ 47 ]. Several molecular markers associated with virus resistance loci in pepper and tomato has been developed to expedite marker-assisted breeding [ 48 , 49 ]. Introgression of resistance genes into cultivated varieties has been the principal route of breeding cultivars that are resistant to viruses such as Tomato yellow leaf virus (TYLCV), Tomato spotted wilt virus (TSWV), Pepper yellow leaf curl virus (PepYLCV) and Chilli veinal mottle virus (ChiVMV) [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several molecular markers associated with virus resistance loci in pepper and tomato has been developed to expedite marker-assisted breeding [ 48 , 49 ]. Introgression of resistance genes into cultivated varieties has been the principal route of breeding cultivars that are resistant to viruses such as Tomato yellow leaf virus (TYLCV), Tomato spotted wilt virus (TSWV), Pepper yellow leaf curl virus (PepYLCV) and Chilli veinal mottle virus (ChiVMV) [ 49 , 50 ]. The major markers linked to tomato yellow leaf disease (TYLCD) that have been developed to date include a closely linked molecular marker, SCAR1, for screening of the Ty-1 locus [ 51 ], P6-25 and FLUW25 for evaluation of Ty-3 , Ty-3a , and Ty-3b loci [ 37 , 50 , 52 ], and SCAR2 and P1-16 for the detection of Ty-2 [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…By combining different resistance genes, pathogens have to overcome multiple resistance mechanisms to break resistance. In this context, combinations of Ty-2 and Ty-3 (an allele of Ty-1 (Verlaan et al, 2013)), or Ty-1 and Ty-2, are used and shown to result in higher resistance level against several geminiviruses (Lee et al, 2021;Prasanna et al, 2015).…”
Section: Resistance Spectrum and Disease Managementmentioning
confidence: 99%